Target antigen screening and development of a multi-component subunit vaccine against Mycoplasma synoviae in chickens - Sun, Xiaomei; Deng, Mingyong; Cheng, Chuxing; Zhao, Ya; Liu, Zuqing; Yang, Yu; Xu, Qiaoxia; Yao, Rong; Hu, Min (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMycoplasma synoviae (MS) is a globally important avian pathogen causing infectious synovitis and respiratory diseases in poultry, leading to significant economic losses. Despite advances in vaccine development, a commercially viable subunit vaccine against MS remains elusive.MethodsWe sequenced whole genomes of six clinical MS strains isolated from different Chinese provinces. Common genes were analyzed using Biopython software, identifying those with high copy numbers in virulent strains and shared among all strains. Vaxign2 and IEDB Antibody Epitope Prediction were used to analyze protein properties. We assessed immune protective effects of candidate proteins and developed a multivalent subunit vaccine.ResultsTen candidate vaccine proteins were initially selected. A multivalent subunit vaccine composed of MSPB, Ppht, Cfba, and EF-G displayed the best protective effect. The optimal immunization dosage was 20μg, with each protein accounting for 25%. The immune production period was determined to be 28 days post-first immunization, lasting 180 days. The immune protection rate against highly virulent strains reached 90%∼100%.DiscussionThis study provides a new approach for screening vaccine antigens and develops an effective candidate vaccine for MS prevention. The multivalent subunit vaccine shows promising results in protecting against MS infections, potentially offering a solution to reduce economic losses in the poultry industry.